If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 34 + -1(x + 8) = 9x + -4 Reorder the terms: 34 + -1(8 + x) = 9x + -4 34 + (8 * -1 + x * -1) = 9x + -4 34 + (-8 + -1x) = 9x + -4 Combine like terms: 34 + -8 = 26 26 + -1x = 9x + -4 Reorder the terms: 26 + -1x = -4 + 9x Solving 26 + -1x = -4 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 26 + -1x + -9x = -4 + 9x + -9x Combine like terms: -1x + -9x = -10x 26 + -10x = -4 + 9x + -9x Combine like terms: 9x + -9x = 0 26 + -10x = -4 + 0 26 + -10x = -4 Add '-26' to each side of the equation. 26 + -26 + -10x = -4 + -26 Combine like terms: 26 + -26 = 0 0 + -10x = -4 + -26 -10x = -4 + -26 Combine like terms: -4 + -26 = -30 -10x = -30 Divide each side by '-10'. x = 3 Simplifying x = 3
| -4m-24=-4(1+6m) | | 25-v-14=9 | | 19=x-5+x | | 3x=68-x | | 16x^3+32x^6+27x^4= | | 6.5=8.9-0.4x | | 0=2z-4 | | 12.44=2g+3.82 | | 6x+2(2x-1)=10 | | .5x+.45(50)=39.5 | | 10.5x=100000 | | 5(6x-6)=60 | | 0.8y+25=-1 | | 6+8q=9+7q | | -7(2x+6)=42 | | (x-10)(x-5)=(x+9)(x+9) | | -6+2x=-6x+34 | | 3x-6=-26-7x | | 12x=4x | | 5n+6n=-99 | | -(x+3)-1=4x+7(x+8) | | 4(x+8)=4(3x+12) | | 17+h-3=-9 | | 3x+2-x=-22 | | 5x+25=13x-7 | | 3.2y-5=3+2(1.4x+4) | | 5.3=9.5-0.6x | | 5m^2+4m=-4 | | 3(3y+1)=9y+39 | | 7-5c=c+27 | | 24=5y+3y | | 4(x+3)+2=2(x-3) |